Design and Synthesis of Novel Antioxidant 2-Substituted-5,7,8-Trimethyl-1,4-Benzoxazine Hybrids: Effects on Young and Senescent Fibroblasts - Theano Fotopoulou; Adamantia Papadopoulou; Andromachi Tzani; Michail Mamais; Eleni Mavrogonatou; Harris Pratsinis; Maria Koufaki; Dimitris Kletsas; Theodora Calogeropoulou (Antioxidants, 2024)
The exponential growth of the aged population worldwide is followed by an increase in the prevalence of age-related disorders. Oxidative stress plays central role in damage accumulation during ageing and cell senescence. Thus, a major target of today’s anti-ageing research has been focused on antioxidants counteracting senescence. In the current work, six novel 5,7,8-trimethyl-1,4-benzoxazine/catechol or resorcinol hybrids were synthesized connected through a methoxymethyl-1,2,3-triazolyl or a 1,2,3-triazoly linker. The compounds were evaluated for their antioxidant capacity in a cell-free system and for their ability to reduce intracellular ROS levels in human skin fibroblasts, both young (early-passage) and senescent. The most efficient compounds were further tested in these cells for their ability to induce the expression of the gene heme oxygenase-1 (ho-1), known to regulate redox homeostasis, and cellular glutathione (GSH) levels. Overall, the two catechol derivatives were found to be more potent than the resorcinol analogues. Furthermore, these two derivatives were shown to act coordinately as radical scavengers, ROS inhibitors, ho-1 gene expression inducers, and GSH enhancers. Interestingly, one of the two catechol derivatives was also found to enhance human skin fibroblast viability. The properties of the synthesized compounds support their potential use in cosmetic applications, especially in products targeting skin ageing.